PERAN ILO ( INTERNATIONAL LABOUR ORGANIZATION ) DALAM MENGATASI PEKERJA ANAK ( CHILD LABOUR ) DI BRAZIL (2008-2013) - Richard Anderson Sinaga; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aims to find out the role of International Labour Organization (ILO) against child labour in Brazil in 2008-2013. ILO is one of the organizations which regulate the labour standards in order to work properly. On the other it also ILO also plays an active role in against child labor. Child labor is one of the social problems which can disrupt the child's mental development and physical development of children. Not only that, children should still be in school but are employed by family economic reasons as well as the poverty that effect their family. The results of this research indicate that the role of the ILO in against child labour in Brazil has shown results. Some roles are made by the ILO through the IPEC program like Social Dialogue protect children from hazardous work in the agricultural sector. ILO-IPEC is also working with the Brazilian government in against child labour as a result of poverty, namely Bolsa Familia Program and provide benefits to poor families in Brazil. As well as the role of the ILO in against child labour, ILO-SSTC (South - South Cooperation Triangle) that Brazil work against child labour with Latin American countries such as Bolivia, Ecuador, and the MERCOSUR countries.Keywords : International Labour Organization (ILO), Child Labour, Social Dialogue, Bolsa Familia, ILO- SSTC ( South – South Triangle Coorperation